Effect of a circular tunnel on ground acceleration responses during earthquakes - Heng, Cheng Song (Nanyang Technological University, 2020)
There has been an increasing number of underground structures being constructed in the recent years and it is known that these structures tend to cause an amplification effect on the surface level of the ground. This paper aims to study the location and size of the tunnel to understand the ground acceleration responses under an earthquake condition. The ground responses were analysed to establish a relationship with the horizontal peak ground acceleration in a case of a seismic condition using the finite element program: PLAXIS 2D. The soil model used to perform the analysis comprises of a single layer of loose sand with a width of 720m. A circular tunnel was also embedded in the 80m thick sand layer with the tunnel located directly at the line of symmetry. Seismic loading from the 2014 Ferndale, California earthquake was used to simulate the earthquake in the context of Singapore. The tunnel parameters carried out in the study include the embedment depth and diameter size. The results gathered revealed that due to the tunnel’s existence, the ground acceleration responses have been amplified. The peak of the amplification tends to be directly above the tunnel or at a close proximity away from the tunnel. As the tunnel is buried further into the ground, the amplification effect became greater. Furthermore, with a larger diameter tunnel, the amplification effect also increases. As the horizontal distance away from the tunnel increases, the amplification effect begins to follow a decreasing trend.